The Language of Nuclear Security: New Case Studies Exploring Online Open-Source Information from Turkey, India, and Jordan - Zenobia S Homan; Shraddha Rane; Yara Shaban; Fadime Ö Özkan; Eunha Yun (International Journal of Nuclear Security, 2023)
This paper presents a novel internet search methodology and new data on the language of nuclear security. Through three case studies (Turkey, India, and Jordan), it describes what openly accessible information exists about nuclear security in a given national context, where more information is needed, and why. In doing so, the paper highlights the importance of documenting the social and geopolitical context of key nuclear concepts. It also examines the role of language and publicly available information on nuclear security and safety to facilitate the articulation and adoption of international best practices. The case studies demonstrate how someone may acquire open-source information on nuclear security through an internet search and how to conduct such a search successfully. Accordingly, it should be possible to apply the presented methodology in any country or language context in the future. Overall, we found that openly available information on nuclear security is scarce, less information is available in the local languages, and mistranslation is a source of confusion. We want to encourage the nuclear community to look beyond internationally dominant languages in acquiring information and in publishing information in the first place, as well as to contribute to clarifying the language of nuclear security and enhance global nuclear security practices.
Keywords: open-source intelligence; nuclear security; language; diversity